Observing secondary school teachers’ effective teaching behavior in the Netherlands, England, and the United States using the ICALT observation instrument - Maulana, Ridwan; Kington, Alison; Ko, James; Feng, Xiangyuan; Helms-Lorenz, Michelle; Looker, Benjamin; Hibbert-Mayne, Kimberley; Blackmore, Karen (Frontiers in Education, 2023)
The purpose of this study was to examine measurement invariance in observer scoring of effective teaching behavior in three secondary education contexts -the Netherlands, England, and the United States. It also aimed to describe what effective teaching behavior looks like in secondary education across the three education contexts. A uniform observation measure called International Comparative Analysis of Learning and Teaching (ICALT) was used to observe teachers. Results revealed that the hypothesized factor structure of effective teaching behavior was confirmed for the Dutch and English data, but not for the US data. Teachers in the Netherlands showed higher levels of more basic teaching behaviors, but lower levels of more complex teaching behaviors, compared to teachers in England. Implications of the findings are discussed.